Kinetics of circulating cell-free DNA for biomedical applications: critical appraisal of the literature. (23rd February 2018) - Khier, Sonia; Lohan, Laura
Circulating cell-free DNA is considered as one of the major breakthroughs in the field of innovative diagnosis, used as a liquid biopsy. The kinetic parameters of a biomarker are mandatory to assess its usefulness as a diagnostic tool. Obtaining precise mathematical values for the kinetic parameters (e.g., half-life) is then crucial because it could be used for therapeutic monitoring as a prognostic factor. However, little is known about the intrinsic properties of circulating cell-free DNA, more especially, its kinetic properties within the organism. We summarized the basic principles that may affect the kinetics of circulating cell-free DNA within the organism in the light of biological and clinical evidence. We also meta-analyzed the reported data in the literature and the methodologies that have been used to study the kinetic parameters of human circulating cell-free DNA in vivo . Lay abstract: Circulating cell-free DNA as a biomarker was a major breakthrough in the field of diagnostics. Understanding the kinetic parameters of a biomarker is mandatory to assess its usefulness as a diagnostic tool, especially for therapeutic monitoring. However, at the present time little is known about its kinetic properties within the organism. This review provides an overview of the basic principles that may impact the kinetics of cell-free DNA within the organism and analyzes the reported data thus far.